IgE, IgG1, and IgG4 Reactivity to Dermatophagoides pteronyssinus Glycosylated Extract in Allergic Patients - Taketomi, Ernesto Akio; Gennari-Cardoso, Margareth Leitão; Sopelete, Monica Camargo; Silva, Deise Aparecida Oliveira; de Almeida, Karine Cristine; Miranda, Juliana Silva; Ynoue, Leandro Hideki; Resende, Rafael de Oliveira; Alves, Ronaldo (BioMed research international, 2019)
Background. House dust mites are important allergen sources and some of these allergenic proteins may contain carbohydrate moieties, which are able to be isolated using lectins, as Concanavalin A (ConA). This study aimed to investigate allergenicity (IgE) and antigenicity (IgG1 and IgG4) of ConA-unbound and ConA-bound Dermatophagoides pteronyssinus (Dpt) crude extracts using sera of mite-allergic patients as well as inhibition capacity of antibody binding. Material and Methods. We obtained mannose-enriched and mannose-depleted fractions from Dpt by ConA affinity chromatography. Both ConA-bound and ConA-unbound fractions were evaluated by ELISA and Western Blotting for specific IgE, IgG1, and IgG4 reactivity with sera obtained from 95 mite-allergic patients (DP+) and 92 nonallergic (NA) subjects. Inhibition ELISA was used to assess cross-reactivity between Dpt extract and its fractions. Results. Among the DP+ patients, no difference was found between ConA-unbound and ConA-bound fractions regarding the levels of specific IgE, IgG1, and IgG4. Nonallergic subjects had the same levels of specific IgG1 to both ConA-unbound and ConA-bound fractions, although for specific IgG4, values were higher for ConA-bound. A positive correlation was found among specific IgE, IgG1, and IgG4 levels when Dpt was compared to ConA-unbound and ConA-bound fractions. Recognition of crude Dpt by IgE, IgG1, and IgG4 was highly inhibited by ConA-unbound and ConA-bound fractions. Western Blotting revealed a broad spectrum of bands ranging from 14 to 116 kDa recognized by specific IgE and IgG4. However, IgG1 reached higher frequency values on high molecular weight polypeptides. Conclusion. ConA-unbound and ConA-bound fractions derived from D. pteronyssinus crude extract revealed important components involved in the IgE recognition in allergic patients as well as IgG1 and/or IgG4 in allergic and healthy subjects.